2021
DOI: 10.32920/ryerson.14643693.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Within These Walls: Exploring the Mental Health Experiences of First Generation South Asian Women in Toronto Canada

Abstract: This research paper explores the mental health experiences of first-generation South Asian women in Toronto, Canada. This research paper starts by providing a brief overview of mental health literature from a South Asian perspective. A qualitative narrative methodology is used to explore what mental health experiences are faced by first-generation South Asian women and their experience of accessing support services in Toronto. Three individual interviews were conducted. Participants were provided with an oppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
2
0
0
Order By: Relevance
“…In another study examining the cultural experience of stigma, the authors found that Indian Australians had a fear of damaging their reputation and social relations and the diagnosis of mental illness will burden older family members (Brijnath & Antoniades, 2018). The fear of being labelled as 'pagal', which is translated to 'crazy' in Hindi language and the fear of being judged, has been discussed by participants in our study: similar to findings in other studies (Atta, 2020;Chahal, 2019).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In another study examining the cultural experience of stigma, the authors found that Indian Australians had a fear of damaging their reputation and social relations and the diagnosis of mental illness will burden older family members (Brijnath & Antoniades, 2018). The fear of being labelled as 'pagal', which is translated to 'crazy' in Hindi language and the fear of being judged, has been discussed by participants in our study: similar to findings in other studies (Atta, 2020;Chahal, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…A similar lack of trust was described by immigrant mothers in relation to the use of interpreters in a study in Australia (Bonakdar Tehrani et al, 2022). Lack of trust and confidence in healthcare workers were also identified as potential barriers to disclosure among immigrants in other studies (Atta, 2020;Jean-Baptiste et al, 2017;Li et al, 2021). One of our participants expressed concerns about the negative social consequences of disclosure, stating that it can even cause problems in finding a suitable life partner for her children in the future.…”
Section: Discussionsupporting
confidence: 66%